Linear epitope identification of monoclonal antibodies against the duck Tembusu virus NS1 - Hantai Tan; Senzhao Zhang; Wangyang Tan; Tao Hu; Yu He; Zhen Wu; Mingshu Wang; Renyong Jia; Dekang Zhu; Mafeng Liu; Xinxin Zhao; Qiao Yang; et al. (Poultry Science, 2023)
ABSTRACT: Since 2010, the duck Tembusu virus (DTMUV) has caused a severe outbreak of egg drop syndrome in laying ducks in China, which has resulted in substantial financial losses in the poultry industry. DTMUV nonstructural protein 1 (NS1), as the only secreted protein, could aid in the development of therapeutic antibodies and diagnostic techniques; however, there are few studies on the preparation and epitope identification of monoclonal antibodies (mAbs) against DTMUV NS1. In this study, by indirect enzyme-linked immunosorbent assay (ELISA), Western blotting, and indirect immunofluorescence assay, we screened 6 mAbs (8A4, 8E6, 10F12, 1H11, 3D5, 5C11) that could specifically recognize DTMUV NS1. For epitope mapping of mAbs, a series of GST-tagged truncated fusion proteins of DTMUV NS1 were constructed by prokaryotic expression. Finally, the 4 shortest linear epitopes were identified by indirect ELISA and Western blotting. The epitope 133FVIDGPK139 was recognized by 8A4, the epitope 243IPKTLGGP250 was recognized by 8E6, the epitope 267PWDEK271 was recognized by 10F12, and 156EDFGFGVL163 was recognized by 1H11, 3D5, and 5C11. By sequence alignment and cross-reaction tests, we found that 8A4 and 8E6 had high specificity for DTMUV NS1 compared with that of other mAbs, but 10F12, 1H11, 3D5, and 5C11 exhibited a clear degree of cross-reaction with dengue virus (DENV), Japanese encephalitis virus (JEV), West Nile virus (WNV), and Zika virus (ZIKV) NS1. Finally, the predicted crystal structure analysis showed the approximate spatial positions of the 4 epitopes on the NS1 dimer. In summary, our study revealed 2 specific mAbs for DTMUV NS1 recognition and 4 multiflavivirus mAbs for DENV, JEV, WNV, and ZIKV NS1 recognition.